A novel tenuivirus infecting wheat in Brazil. - PEREIRA, F. S. (2022)
Since 1948, pale yellow wheat spike have been reported in southern Brazil. This symptom was associated with tenuiviruses due to the observation of cytoplasmic inclusions constituted by a mass of filamentous particles (7?10 nm in diameter) with indeterminate length, identical to those found in ?leaf dip? preparations. Such symptoms are still seen in wheat crops; how- ever, there is a lack of information regarding this pathosystem. Decades after the first report, the first sequences of wheat white spike virus were characterized. Wheat plants with symptoms such as pale yellowing, chlorotic streaks, and leaf mosaic were collected in Paraná State, Southern Brazil. High-throughput sequencing was used to determine the nearly complete nucleotide sequence of the viral genome. The genome is composed of five RNAs with a total size of 18,129 nucleotides, with eight open reading frames (ORFs). The virus identified in this study can be included in a new species in the family Phenuiviridae, genus Tenuivirus, and we have tentatively named this virus ?wheat white spike virus?.